Cabinet Reshuffle News for 2020 in Van Leeweun's Critical Discourse Analysis - Dedi Sahputra (Polit Journal Scientific Journal of Politics, 2021)
Political events, especially those related to public policy, are the consumption of mass media to be presented in the form of news to the public. In reconstructing events into news, the mass media has the potential to be influenced by various interested parties. Theo Van Leewuen's critical discourse analysis is a model that can be used to critically analyze the effects that occur in the presentation of news in the mass media. Through text analysis, this critical discourse analysis model will inform about the various strategies used in compiling news texts. The object of this research is kompas.com news entitled "Jokowi Announces Reshuffle, These are 6 New Ministers of the Advanced Indonesian Cabinet" using a descriptive qualitative method. The result shows that there is differentiation or differences in treatment in the presentation of news about the resuffle of Ministers of the Forward Indonesia Cabinet by the Joko Widodo administration regime. This differentiation has an impact on the different images and impressions in the news, thus indicating political interests in the text presented.